The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/ase.1444
|View full text |Cite
|
Sign up to set email alerts
|

Modified team‐based learning strategy to improve human anatomy learning: A pilot study at the Universidad del Norte in Barranquilla, Colombia

Abstract: As part of an institutional program sponsored by the Centre for Teaching Excellence at the Universidad del Norte, Barranquilla, Colombia, we developed an educational research study on two sessions of human anatomy in which we combined team-based learning (TBL) and the use of iPads. Study data included the TBL, assessments applied during the course, student's grades on mid-term examinations and students' perceptions of their experiences. Students reported a positive attitude toward the use of the TBL sessions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 31 publications
(52 reference statements)
1
25
0
2
Order By: Relevance
“…The incorporation of TBL improved student perceptions towards teamwork, in addition to improving performance on summative assessments (Huitt et al, 2015). Finally, the introduction of TBL to an anatomy program resulted in significant positive correlations between formative IRAT scores and midterm assessments, as well as improvement in formative IRAT and GRAT performances over time (Martinez and Tuesca, 2014).…”
Section: Anatomical Sciences Education September/october 2015mentioning
confidence: 96%
See 1 more Smart Citation
“…The incorporation of TBL improved student perceptions towards teamwork, in addition to improving performance on summative assessments (Huitt et al, 2015). Finally, the introduction of TBL to an anatomy program resulted in significant positive correlations between formative IRAT scores and midterm assessments, as well as improvement in formative IRAT and GRAT performances over time (Martinez and Tuesca, 2014).…”
Section: Anatomical Sciences Education September/october 2015mentioning
confidence: 96%
“…This is particularly evident in Canadian medical schools, where less than half of schools surveyed reported including time-intensive dissection in the mandatory curriculum (Ovsenek, 2013). The challenges of teaching anatomy in substantially reduced time has necessitated adaptations and innovations to teaching strategies, including the development and incorporation of teaching technology in the anatomy laboratory (Mayfield et al, 2013;Benninger et al, 2014;Martinez and Tuesca, 2014), the move towards a systems-based approach where anatomy teaching is integrated with other disciplines in the curriculum (Bergman et al, 2014), and the implementation of team-based learning (TBL) to anatomy education (Neider et al, 2005;Vasan et al, 2005). Traditional aspects of TBL (Michaelsen, 2002) that have been transferred to the anatomy laboratory include: pre-laboratory assignments, the use of individual-and group-readiness assurance tests (IRATs, GRATs) at the onset of the small-group laboratory exercise, and the opportunity for immediate feedback, review and discussion regarding IRAT and GRAT responses in the small groups, all prior to the small group laboratory activity/application problem (Neider et al, 2005;Vasan et al, 2005Vasan et al, , 2009Vasan et al, , 2011.…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies have examined the incorporation of iPads in anatomy courses in both undergraduate and medical school settings (Mayfield et al, ; Martinez and Tuesca, ; Stewart and Choudhury, ; Lynn et al, ; Meyer et al, ; Morris et al, ; Raney, ; Wilkinson and Barter, ). The incorporation of iPad muscle and skeletal system anatomy apps in an undergraduate anatomy and physiology laboratory that employed a survey of 52 students found that the use of iPads in the classroom enhanced the student learning experience, encouraged student collaboration, helped the students to learn the course material, and concluded that students had an overall positive response to the use of these anatomy apps (Lynn et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the students preferred the iPads over a standard paper laboratory manual and anatomy atlases. Martinez and Tuesca () surveyed medical students following the incorporation of iPad apps in an anatomy course and found that the students thought iPads fostered team‐based learning and helped them to learn the course material. Raney (), focusing on the introduction of iPads and anatomy apps in a one‐semester human anatomy course, concluded that student learning improved when iPads were incorporated throughout the course, but this improvement only occurred when students had unlimited access to iPads.…”
Section: Introductionmentioning
confidence: 99%
“…As well as CL, other examples of activelearning strategies that place a greater emphasis on studentcentered learning rather than instructor-centered activities; include team-based learning (TBL) and problem-based learning (PBL) (Sugand et al, 2010;Bloodgood, 2012;Wright, 2012;Davidson and Major, 2014;Michaelsen et al, 2014;Wolff et al, 2015;Gross et al, 2017). To date, most activelearning approaches adopted to teach anatomy in both undergraduate and graduate medical disciplines have primarily been based on TBL which aims to: (1) oblige students to study more consistently, (2) provide regular feedback on their preparedness, (3) give them the opportunity to develop higher reasoning skills, (4) reinforce self-directed learning, and (5) foster an appreciation with peer respect (Nieder et al, 2005;Vasan et al, 2008Vasan et al, , 2009Thomas et al, 2011;Inuwa, 2012, Mart ınez andTuesca, 2014;Gross et al, 2017). However, TBL is a form of "flipped classroom" in which successful learning requires completion of prework which students may not be motivated to engage in (Kenwright et al, 2016).…”
Section: Introductionmentioning
confidence: 99%